IN VITRO ANTIBACTERIAL ACTIVITY OF MEDICINAL PLANTS IN THE CENTRAL NORTH OF MOROCCO: A POSSIBLE SOURCE OF ALTERNATIVE DRUGS AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - ZEOUK, IKRAME; OUALI LALAMI, ABDELHAKIM EL; BEKHTI, KHADIJA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aims the investigation of the antimicrobial potential of medicinal plants selected in the central north of Morocco against methicillin-resistant Staphylococcus aureus and Staphylococcus epidermidis strain often involved in dermatitis. Methods: Structured interviews were carried out among 91 herbalists and traditional healers through a specific information questionnaire, the in vitro susceptibility of Staphylococcus strains award ethanol extracts was evaluated using the well-diffusion assay, while the agar-microdilution method was used to determinate the minimal inhibitory concentrations (MIC). The total phenolic and flavonoids contents of all tested extracts were also determined. Results: Based on the ethnobotanical survey, a total of 55 plant species belonging to 30 families were mentioned. The Lamiaceae family was the most represented (18.80%) followed by the Apiaceae family (10.90%). Leaves (45.00%) were the favored used part. Decoction method (48.53%) was the most frequently used to prepare remedies that are taken externally (75.00%). Nine of the 17 most selected species have shown an effective antistaphylococcal activity; the most active extracts were Punica granatum and Rhamnus alaternus with MIC values ranging between 0.25 mg/ml and 2.00 mg/ml. Conclusion: The current data confirm the good antistaphylococcal activity of P. granatum and R. alaternus and suggest that these species could constitute a promoter source for antistaphylococcal drugs with deeply studies.